2021
DOI: 10.1177/0011128721999347
|View full text |Cite
|
Sign up to set email alerts
|

Out of the Picture: Latinx and White Male Youths’ Facial Features Predict Their Juvenile Justice System Processing Outcomes

Abstract: Adults’ facial characteristics predict whether and how severely they are sentenced in the adult criminal justice system. We investigate whether characteristics of White and Latinx male youths’ faces predict the severity of their processing in the juvenile justice system. Among a sample of first-time offenders, despite no differences in the severity of their offenses, youth who were perceived by naïve observers as more dominant, less trustworthy, less healthy, and having darker skin were more likely to receive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…According to recent research, judges may bear implicit biases that can impact judicial judgment (Rachlinski et al, 2009). For example, Chen et al (2021) found that youth who were perceived as more dominant, less trustworthy, less healthy and having darker skin had a higher probability of receiving harsher sentences (Chen et al, 2021). In their study of adjudication decision-making, using data from the University of Michigan's Child and Adolescent Data Lab, Evangelist et al (2017) found non-legal factors such as age, race, and gender were associated with adjudication decision-making, controlling for legal factors including offense type and severity, and offending history.…”
Section: Child Delinquency In the Juvenile Justice Systemmentioning
confidence: 99%
“…According to recent research, judges may bear implicit biases that can impact judicial judgment (Rachlinski et al, 2009). For example, Chen et al (2021) found that youth who were perceived as more dominant, less trustworthy, less healthy and having darker skin had a higher probability of receiving harsher sentences (Chen et al, 2021). In their study of adjudication decision-making, using data from the University of Michigan's Child and Adolescent Data Lab, Evangelist et al (2017) found non-legal factors such as age, race, and gender were associated with adjudication decision-making, controlling for legal factors including offense type and severity, and offending history.…”
Section: Child Delinquency In the Juvenile Justice Systemmentioning
confidence: 99%
“…However, our results also clearly emphasize the importance of racial/ethnic categorization that captures distinctions between subgroups which generally has been overlooked. Though some research on phenotype and skin tone variation between and within racial/ethnic groups has demonstrated the relevance of these factors (e.g., Chen et al 2021; King and Johnson 2016; White 2015), absent from most prior work is an explicit consideration of racial/ethnic subgroup memberships that might have import for the mobilization of social control in certain contexts. Accordingly, we encourage cooperation between researchers and agencies in the development of data collection procedures that capture race and ethnicity in more nuanced ways.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, due to the globalization of race relations, the traditional biracial divide in the U.S. has become increasingly eclipsed by a fluid rank-ordering of groups according to easily perceptible physical characteristics; consequently, “color gradations, which have always been important matters of within-group differentiation, will become more salient factors of stratification” (Bonilla-Silva 2018:185; see also Khanna 2012; Morning 2018). The literature on colorism and experiences of discrimination associated with darker skin is extensive (e.g., Hunter 2007; Monk 2015; Weaver 2012), and recent evidence indicates that individuals with darker skin tones and Afrocentric facial characteristics are disadvantaged with regard to a wide array of justice system outcomes (Burch 2015; Chen et al 2021; King and Johnson 2016; Monk 2019; White 2015). Accordingly, as some prior research has indicated (Blake et al 2017; Hannon et al 2013), disparities in school discipline across racial/ethnic subgroups might be patterned in ways that suggest the existence of nebulous racial groupings corresponding with “reflected race” (Gonlin 2020; Khanna 2010) rather than clear and precise distinctions.…”
Section: Theoretical Accountsmentioning
confidence: 99%
“…First, we examined whether intraindividual changes in neighborhood white concentration across adolescence had implications for developmental changes in internalizing and externalizing in a sample of U.S. Mexican adolescents that were diverse on nativity, gender, and neighborhood socioeconomic and racial contexts. Unfortunately, given the role of colorism in policing, surveillance, and belonging (Chen, Fine, Norman, Frick, & Cauffman, 2021), we were not able to account for within‐group skin‐tone diversity among the U.S. Mexican youth in our sample. This is an important area for future research, though we note that other aspects of phenotypic differences (e.g., accents, language spoken, social affiliations, signs, and symbols) can also prompt inspection, surveillance, gatekeeping, and othering.…”
Section: Discussionmentioning
confidence: 99%